English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

What exacly are you suppose to do to solve the equation?
For example, let's say f(x) = x^2+2 and g(x)= 6x+4

2006-12-12 04:52:51 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

(f ◦ g)(2) means f(g(2))

so this would be f(g(2)) = (6x+4)^2+2 = 258

2006-12-12 04:59:42 · answer #1 · answered by Anonymous · 0 0

The equation is read "f of g of 2" which means you work the g(x) equation with x being 2, and then you put the answer to the g(x) equation into the f(x). In this case, g(2) = 6(2) + 4, so g(2) = 16, then you would put 16 as x in the f(x) equation.

2006-12-12 05:03:13 · answer #2 · answered by Michael L 2 · 0 0

For f composed of g, write g(x) for x in f.
f[g(x)] = [g(x)]^2 + 2
=[(6x+4)^2 + 2
f[g(2)] = (12+4)^2 + 2
= ...

2006-12-12 05:12:33 · answer #3 · answered by S. B. 6 · 0 0

combine the 2 funtions to gether into 1 like so x^2 + 6x + 8 = 0
which make the form ax^2 +bx + c = 0 use quadratic equation to solve for x twice. x = -b + or - sqr(b^2 - 4ac)/2a

That's how I would do it because the and between the 2 functions make me thing that you are suposed to add them together, but I could be wrong.

2006-12-12 05:07:15 · answer #4 · answered by ikeman32 6 · 0 1

(f o g)(2) just means to apply the functions in the order of the brackets.

In this case, (f o g)(2) is the same as f(g(2)).

This just means you plug in g(2) for every occurrence of x in the function.

f(g(2)) = (g(2))^2 + 2

And then solve for g(2) normally.

f(g(2)) = [6(2)+4]^2 + 2
f(g(2)) = [16]^2 + 2

2006-12-12 05:00:30 · answer #5 · answered by Puggy 7 · 0 0

fedest.com, questions and answers